Australia calls you settler, investor or tourist - Trompf, Percy, 1902-1964.; Australian Railways Commissioners ([Sydney : Australian Railways Commissioners, 1928)
An overseas campaign targeting settlers, tourists and investors in Great Britain, United States, South Africa, Canada to come to Australia which included this poster by Percy Trompf. In addition a pamphlet entited Australia calls you : the continent of opportunity. Sometimes accompanied by the smaller booklet.
Caption title.
"Get booklet Australia calls you ..."
Poster signed: Trompf.
Artwork featuring in the foreground a standing globe showing Australia coloured red as a member of the British Empire casting a shadow. In the background a country scene featuring a gum tree, a wooden fence running beside a lane with blue-pink mountains in the background. In hues of orange, brown and green. The sky is orange.
Digital master available
Exhibited: NLA Treasures Gallery, Treasures, The Sell, 23 November 2016 – 25 April 2017
Keywords: Travel posters, Australian; Travel posters -- Australia; Australia -- Description and travel -- 1901-1950.; Australian